Arkansas River Basin water forum: "a river of dreams and realities": proceedings of the 1995 Arkansas River Basin water forum - Colorado Water Resources Research Institute, author (Colorado State University. Libraries, 1995)
Arkansas River Basin water forum was held on January 17-18, 1995 in Pueblo, Colorado.
A river of dreams and realities
Abstracts of papers presented.
November 1995.
Keywords: Water resources development -- Arkansas River Watershed -- Congresses; Watershed management -- Arkansas River Watershed -- Congresses; Resource allocation -- Congresses